The Lord's coming, Israel and the church - Baines, Thomas Blackburn, 1832-1891 (London, UK G. Morrish)
Includes index.
Brethren writer. Copy one donated by Mrs F.F. Hunter. Copy two well annotated. (Previous owner penned date published as 1934.)
Keywords: Eschatology